Hubungan Perilaku Perawat Dengan Pelaksanaan Terapi Aktivitas Kelompok Pada Klien Halusinasi Pendengaran di RS Jiwa di Kota Palembang - Leny Joice Sianturi; Ria Dila; Dwi Apriani; Tri Febrianti (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Group activity therapy (GAT) is a nursing modality therapy aimed at groups of clients with similar problems. Activities are used as therapy, and groups are used as targets of care. Improving nurses' ability to implement TAK can be obtained through formal education or continuing nursing education. The study aims to determine the relationship between knowledge, attitudes, and actions of nurses with the implementation of group activity therapy in hallucination clients. group activity therapy on auditory hallucination clients. The research method used quantitative analytical research. Samples were taken using purposive sampling technique, namely nurses who served in the inpatient room at the Mental Hospital in Palembang City. 30 people were sampled. In this study, it was found that there was a relationship between nurses' knowledge and the implementation of GAT, this was in accordance with the chi square test with p (0.047) < ? (0.05), and there was also a relationship between nurses' attitudes and the implementation of GAT based on the chi square test with p (0.023) < ? (0.05). In addition, it was also found that there was a relationship between nurse actions and the implementation of GAT based on the chi square test p (0.011) < ? (0.05).